2023
DOI: 10.3389/fphar.2022.1120043
|View full text |Cite
|
Sign up to set email alerts
|

Association between fibrinogen/albumin ratio and arterial stiffness in patients with type 2 diabetes: A cross-sectional study

Abstract: Background: Fibrinogen albumin ratio (FAR) is significantly correlated with the severity and prognosis of cardiovascular disease (CVD). Arterial stiffness is an early lesion of CVD, but no studies have examined the correlation between arterial stiffness and FAR. This study aimed to examine the relationship between FAR and arterial stiffness in patients with type 2 diabetes (T2D), as measured by brachial-ankle pulse wave velocity (baPWV).Methods: In this cross-sectional investigation, patients with T2D were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Prior cross-sectional studies have identified significant associations between PWV and ESR ( 48 ) FGN ( 49 ) and TWBC ( 17 , 50 ) based on cross-sectional data. Our longitudinal study may serve to validate this existing evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Prior cross-sectional studies have identified significant associations between PWV and ESR ( 48 ) FGN ( 49 ) and TWBC ( 17 , 50 ) based on cross-sectional data. Our longitudinal study may serve to validate this existing evidence.…”
Section: Discussionmentioning
confidence: 99%
“… 8–10 Meanwhile, FAR was also reported to be closely related to the severity and prognosis of acute coronary syndrome. 11 In recent years, studies have reported that FAR is associated with poor prognosis of lacunar infarction, pontine infarction, and hemorrhagic transformation (HT) after IVT in ischemic stroke patients. 12–14 Nevertheless, the correlation between FAR and END after IVT has not been reported.…”
Section: Introductionmentioning
confidence: 99%